Pediatric trapdoor fracture of the orbital floor with Tear-Drop sign: A case report - Zakariae Hakkou; Zainab El Zouiti; Fahd Elayoubi; Adil Abdenbi Tsen (Radiology Case Reports)
Orbital trapdoor fractures are a unique type of blowout fracture seen predominantly in children due to their elastic bone structure, which predisposes to soft tissue entrapment and symptoms such as diplopia. These injuries, often termed “white-eyed blowout” fractures due to the absence of significant external signs, demand careful clinical and radiological evaluation. We present the case of a 15-year-old male who experienced diplopia and restricted upward gaze following blunt trauma to the left eye. Despite the lack of periorbital edema or hemorrhage, CT imaging revealed inferior rectus muscle entrapment, characterized by the tear-drop sign. Emergency surgical intervention within 8 hours successfully released the entrapped muscle, and a Vicryl mesh was placed to prevent re-entrapment. Postoperative care included anti-inflammatory treatment, with follow-up demonstrating significant improvement in ocular mobility and resolution of diplopia. This case underscores the critical role of prompt recognition, high-resolution CT imaging, and timely surgical intervention in the management of pediatric orbital trapdoor fractures to prevent long-term functional impairments.